Targeting Intensive Job Assistance to Ex-Offenders by the Nature of Offense: Results from a Randomized Control Trial - Christopher R. Bollinger; Aaron Yelowitz (Institute of Labor Economics (IZA), 2021)
As many as two-thirds of newly-released inmates will be arrested for a new offense within three years. This study evaluates the impact of job assistance on recidivism rates among ex-offenders. The job assistance program, run though the private company America Works, uses a network of employers to place clients. Ex-offenders were randomly assigned to intensive job assistance (treatment group) or the standard program (control group). The intensive program is meant to improve average work readiness for ex-offenders. It reduces the likelihood of subsequent arrest among non-violent ex-offenders, but has little effect on violent ex-offenders. The re-arrest rate for non-violent ex-offenders in the treatment group was 19 percentage points lower than those in the control group. The re-arrest rate for violent ex-offenders in the treatment group was indistinguishable from those in the control group. We estimate benefits from intensive job assistance from averted crimes and find that they outweigh the 5,000 up-front cost for non-violent ex-offenders.
Keywords: J48; 330; criminal recidivism; rapid workforce attachment